Phos-tag-based phosphate affinity chromatographic techniques - Emiko Kinoshita-Kikuta; Eiji Kinoshita; Tohru Koike (Journal of Chromatography Open, 2022)
For phosphoproteomics, it is important to separate and enrich phosphoproteins from complex biological samples predominantly containing their nonphosphorylated counterparts. This review describes effective chromatographic techniques for the separation and enrichment of phosphoproteins using a unique functional molecule, Phos-tag, which can capture a phosphate monoester dianion in an aqueous solution at neutral pH, developed by mimicking the active center of alkaline phosphatase. Phosphate affinity chromatographic Phos-tag agarose and Phos-tag magnetic beads can be used for the comprehensive enrichment of phosphoproteins under near-physiological conditions, providing information on the nature of native phosphoproteins in cells. The simple procedure using the Phos-tag beads facilitates the efficient enrichment of rare phosphoproteins from complex mixtures, resulting in increased sensitivity of downstream assays. These affinity beads can also be used for the enrichment of phosphopeptides in phosphorylation analysis using mass spectrometry. Phosphopeptide enrichment must be employed to decrease the complexity of the proteome, for which several strategies have been proposed. We introduce the performance of Phos-tag beads compared with other conventional strategies proposed for phosphopeptide enrichment and the impact of Phos-tag-based affinity chromatography for phosphoproteomics.